Genética Forense: uma ferramenta para a conservação da fauna dos Campos Gerais do Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The environmental threats derived from the human interventions on ecossystems, such as habitat loss and fragmentation, biological invasions, illegal and abusive hunting, and animal trafficking and smuggling, impairs conservation efforts directed to brazilian biodiversity. In this context, concerns about fauna protection and illegal trafficking control come together with the emergence of new acessory technologies applied on criminal investigations related to wildlife trade. The methods of genetic evaluation of organisms or animal-derived products stands out as a relevant tool species differentiation, contributing for the establishment of forensic genetic applied to crimes against wildlife. The goal of the present study was to verify the accuracy of molecular identification of terrestrial vertebrate species based on COI gene (Cox-1) sequencing, as well as to realize a survey of the legal framework of the Parana state turned to the use of forensic genetic techniques on investigations of environmental crimes against the fauna. For this purpose, two samples of muscular tissue were blinded obtained from the CETAS Ponta Grossa and submitted to AND extraction according to the adapted phenol-chloroform method, followed by Cox-1 gene amplification using PCR, sequencing, and identification. The confirmation of the consensus identity from the sequences obtained was held by the comparision with sequences from open data banks (BOLD System and NCBI). Legal regulations of Parana state were assessed using the Sistema Estadual de Legislação do Estado do Paraná. For the two samples, the molecular identification confirmed (99,99%) that the muscular tissue belong to the PHYLUM Chordata, CLASS Mammalia, ORDER Artiodactyla, FAMILY Cervidae, GENUS Mazama SPECIE Mazama gouazoubira. In turn, the survey of the state legal framework suggests the existence of a legal uncertainty in respect to the forensic genetic services application on crimes against fauna.
Keywords: Campos Gerais; Crimes Ambientais; Legislação Ambiental; Genética Forense; DNA Mitocondrial; Campos Gerais; Environmental Crimes; Environmental Law; Forensic Genetic; Mitochondrial AND; CNPQ::CIENCIAS BIOLOGICAS